Evolutionary modelling in economics: a survey of methods and building blocks - Karolina Safarzynska; Jeroen C.J.M. van den Bergh (Max Planck Institute of Economics, 2008)
In this paper we present an overview of methods and components of formal economic models employing evolutionary approaches. This compromises two levels: (1) techniques of evolutionary modelling, including multi-agent modelling, evolutionary algorithms and evolutionary game theory; (2) building blocks or components of formal models classified into core processes and features of evolutionary systems - diversity, innovation and selection - and additional elements, such as bounded rationality, diffusion, path dependency and lock-in, co-evolutionary dynamics, multilevel and group selection, and evolutionary growth. We focus our attention on the characteristics of models and techniques and their underlying assumptions.
Keywords: B52; C60; C73; 330; bounded rationality; evolutionary algorithms; evolutionary game theory; evolutionary growth; innovation; multilevel evolution; neo-Schumpeterian models.; Evolutionsökonomik; Wirtschaftsmodell; Theorie